Niclosamide's potential direct targets in ovarian cancer. Issue 2 (14th April 2021) - Sekulovski, Nikola; MacLean, James A; Bheemireddy, Sambasiva R; Yu, Zhifeng; Okuda, Hiroshi; Pru, Cindy; Plunkett, Kyle N; Matzuk, Martin; Hayashi, Kanako
Abstract: Recent evidence indicates that niclosamide is an anti-cancer compound that is able to inhibit several signaling pathways. Although niclosamide has previously been identified by high-throughput screening platforms as a potential effective compound against several cancer types, no direct binding interactions with distinct biological molecule(s) has been established. The present study identifies key signal transduction mechanisms altered by niclosamide in ovarian cancer. Using affinity purification with a biotin-modified niclosamide derivative and mass spectrometry analysis, several RNA-binding proteins (RBPs) were identified. We chose the two RBPs, FXR1 and IGF2BP2, for further analysis. A significant correlation exists in which high-expression of FXR1 or IGF2BP2 is associated with reduced survival of ovarian cancer patients. Knockdown of FXR1 or IGF2BP2 in ovarian cancer cells resulted in significantly reduced cell viability, adhesion, and migration. Furthermore, FXR1 or IGF2BP2 deficient ovarian cancer cells exhibited reduced response to most doses of niclosamide showing greater cell viability than those with intact RBPs. These results suggest that FXR1 and IGF2BP2 are direct targets of niclosamide and could have critical activities that drive multiple oncogenic pathways in ovarian cancer. Abstract : FXR1 and IGF2BP2 are direct targets of niclosamide and could have critical activities that drive multiple oncogenic pathways in ovarian cancer.